2001
DOI: 10.3354/meps224093
|View full text |Cite
|
Sign up to set email alerts
|

Patch recolonization by the tunicate Pyura praeputialis in the rocky intertidal of the Bay of Antofagasta, Chile: evidence for self-facilitation mechanisms

Abstract: Patch dynamics of intertidal Pyura praeputialis (Heller, 1878) were studied in experimentally cleared plots at 3 vertical levels (upper, mid and lower P. praeputialis levels) and 3 sites within the Bay of Antofagasta, Chile. The sites corresponded approximately to the northern limit (Las Conchillas), the center (El Way), and the southern limit (El Lenguado) of the species geographic distribution in Chile. Replicated 40 × 60 cm quadrats were photographed periodically to follow patch re-colonization. Patch reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
2
25
0
1
Order By: Relevance
“…These include: (1) interference, by providing nursery areas for juveniles which offer protection against predation (for gastropods and decapods, including species which are exploited by intertidal food-gathers; Varas 1996, Fairweather 1991, (2) increasing the chance of survival, by reducing the risk of desiccation for species without external protection (i.e. Polychaeta, Nemertea; Cerda & Castilla 2001), (3) positive interactions among species, since more diverse communities may have enhanced ecosystem functions (Chapin et al 1998, Stachowicz 2001, (4) coexistence mediated by spatial and temporal variation in recruitment (Chesson 1986), given that the disturbance regime and patch dynamics of P. praeputialis in Antofagasta may promote the coexistence of fugitive species, both inside and on top of the ascidian matrices (Alvarado et al 2001, Monteiro et al 2002. Future experimental work should address such issues to understand how the species diversity patterns described here and the role of the P. praeputialis matrices are linked by the mechanisms above.…”
Section: Discussionmentioning
confidence: 99%
“…These include: (1) interference, by providing nursery areas for juveniles which offer protection against predation (for gastropods and decapods, including species which are exploited by intertidal food-gathers; Varas 1996, Fairweather 1991, (2) increasing the chance of survival, by reducing the risk of desiccation for species without external protection (i.e. Polychaeta, Nemertea; Cerda & Castilla 2001), (3) positive interactions among species, since more diverse communities may have enhanced ecosystem functions (Chapin et al 1998, Stachowicz 2001, (4) coexistence mediated by spatial and temporal variation in recruitment (Chesson 1986), given that the disturbance regime and patch dynamics of P. praeputialis in Antofagasta may promote the coexistence of fugitive species, both inside and on top of the ascidian matrices (Alvarado et al 2001, Monteiro et al 2002. Future experimental work should address such issues to understand how the species diversity patterns described here and the role of the P. praeputialis matrices are linked by the mechanisms above.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that in Antofagasta, the described bio-foam also enhances local tunicate settlement, because tadpole larvae of P. praeputialis are in the plankton for Ϸ2 h (18), less than the persistence of the bio-foam associated with P. praeputialis. Furthermore, this may be one of the mechanisms responsible for the as yet unexplained restricted distribution of this free-spawning species inside the Antofagasta Bay, as well as for its high settlement success on adult conspecifics inside the bay (19). Additionally, preliminary field observations in the intertidal rocky shores of Las Cruces and Pelancura (central Chile) have shown that a similar bio-foam production also occurs concurrently with massive gamete spawning of the sunstar Heliaster helianthus and for the chiton Acanthopleura echinata.…”
Section: Resultsmentioning
confidence: 99%
“…ship hulls) and/or sea rafting from extant populations in Australia . Inside the Antofagasta Bay, P. praeputialis shows high densities Alvarado et al 2001). The species is highly competitive for primary substrata , and in the part of the rocky mid-intertidal fringe at Antofagasta outcompetes the native mussel Perumytilus purpuratus.…”
Section: Well-documented Non-indigenous Speciesmentioning
confidence: 97%